2019
DOI: 10.1371/journal.pone.0225863
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of fowl adenovirus isolate of Malaysia attenuated in chicken embryo liver cells and its pathogenicity and immunogenicity in chickens

Abstract: Fowl adenovirus (FAdV) is the causative agent of inclusion body hepatitis (IBH) in chickens with significant economic losses due to high mortality and poor production. It was objectives of the study to attenuate and determine the molecular characteristic of FAdV isolate (UPM1137) of Malaysia passages in primary chicken embryo liver (CEL) cells. The cytopathic effect (CPE) was recorded and the present of the virus was detected by polymerase chain reaction (PCR). Nucleotide and amino acid changes were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In addition, FAdV virus isolation was carried out using primary CEL and cytopathic effects were noticed after 24 hours of virus inoculation in the form of cell rounding and small focal cells' areas detachment from the surface. Similar CPE in CEL of FAdVs was previously described by (Soumyalekshmi et al, 2014;Mohamed Sohaimi et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, FAdV virus isolation was carried out using primary CEL and cytopathic effects were noticed after 24 hours of virus inoculation in the form of cell rounding and small focal cells' areas detachment from the surface. Similar CPE in CEL of FAdVs was previously described by (Soumyalekshmi et al, 2014;Mohamed Sohaimi et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, outbreaks of IBH-HPS have hit several countries over the globe such as Japan (Nakamura et al, 2011), Malaysia (Mohamed Sohaimi et al, 2019), China (Li et al, 2018), India (Raj et al, 2018;Suohu et al, 2021) Spain (Oliver-Ferrando et al, 2017), Iran (Morshed et al, 2017), South Africa (Maartens et al, 2014) and Saudi Arabia (Hemida and Alhammadi 2017). The disease mortalities reach 5-10% and may surge to 30% if it is co-infected with other immunosuppressive agents, such as Chicken infectious anemia virus CIAV and Infectious bursal disease virus (IBDV) (McFerran and Smyth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, molecular characterization and phylogenetic studies of recent FAdV isolates from clinical cases in Malaysia revealed FAdV-8b as the predominant serotype behind IBH outbreaks among commercial broilers, similar to South Korea [48]. Interestingly, Malaysia does not have a history of FAdV outbreaks caused by serotypes other than FAdV-8b, which may be attributable to Malaysia being a self-sufficient producer that does not rely on international trade for poultry products, thus limiting the introduction of other serotypes [87][88][89]. That is, the Malaysian FAdV-8b cases may be ascribable to the "carry-over" or dissemination of viruses by wild birds; this may also apply to the Korean FAdV-8b cases that surged, although these assumptions require further corroboration.…”
Section: Current Status and Future Perspectivesmentioning
confidence: 99%
“…FAdV-4 is the primary pathogen of HHS, which has an immunosuppressive potential ( 51 , 52 ). Previous studies have shown that apoptosis and inflammatory signaling activation are potent inducers of immunosuppressive mechanisms ( 4 , 53 ).…”
Section: Discussionmentioning
confidence: 99%